Keanekaragaman Pertumbuhan dan Hasil Tanaman Oyong (Luffa Acutangula L.) pada Berbagai Konsentrasi Kolkhisin - Adib Fauzan Rahman; Nandariyah Nandariyah; Parjanto Parjanto (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2017)
Oyong production is still low due to the limited availability of quality seeds. The production can be increased by one of the plant breeding techniques, which is mutation technique. The technique of mutation by chemical mutagens is able to increase the genetic diversity ofplants allowing the breeding to select genotype of plants in accordance with the intended breeding objective. Therefore, research is required to be conducted by using colchicin as a chemical mutagen which causes polyploid, in which organism has three sets or more chromosomes inside its cells. Meanwhile, the general nature of this polyploid plant is being sturdier; parts of the plantare bigger; so that later, its poor nature will be better as well as changing the potency of the result. Research using complete randomized block design (RBD) with one factor concentration of 0,1% (P1), 0,2% (P2), 0,3% (P3), 0,4% (P4), 0,5% ( P5), and 0,6% (P6). Colchicines treatment can cause changes in growth and yield variables. Colchicines treatment with a concentration of 0,3% showed positive changes to theweight of fruit, fruit diameter and length of the fruit. An increase in diversity on growth and yield components especially on colchicines treatment with 0,3%concentration.